Resistance to Change: Overcoming Institutional and Individual Limitations for Improving Student Behavior Through PLCs - Maag, John W. (Journal of the American Academy of Special Education Professionals, 2009)
Many public schools currently have organizational structures that form barriers for dealing more effectively with students’ challenging behaviors even though positive school-wide approaches exist and provide empirical support for their use. Nevertheless, resistance to change occurs at both institutional and individual levels. Improving student behavior and learning requires a paradigm shift away from teachers working in isolation to working together. Professional growth also must shift away from oneshot inservices to more intense and long-term training. One method for achieving this type of paradigm shift is through the use of professional learning communities (PLCs). Through these communities, schools can challenge existing paradigms and explore the possibilities that positive supports offer to dealing with students’ challenging behaviors. Therefore, the purpose of this article is to describe prominent and misconceived beliefs that contribute to institutional and individual resistance and suggest professional learning communities (PLCs) as a means for moving past this resistance in a collaborative and empowering way to improve student behavior and learning.